(untitled) (Journal of history, 2020)
The article «Financial support for agriculture of the KazASSR in 192030» highlights specific issues of agriculture construction and organization of financing in the Soviet period. It describes the most important areas of financial support of agriculture. It also considers some of the taxation issues of agriculture of the republic, in particular, it analyzes issues related to the introduction of the hard agricultural tax in the initial stages of creating a new agricultural sector (1922-29) especially intensified in 1927-1929. The indigenous people, the Kazakhs were not prepared for the agricultural tax in this period. The land tax from the peasants also exceeded the permissible norm. Since Kazakhstan was purely animal-husbandry country during this period and the ill-conceived tax rate exceeded the permitted limit, which led later to the tragic consequences of the indigenous people. Key words: Taxation, local budget, financial support for agriculture, settling, collectivization, the collective farm subsidy system